The impact of time management on the success of service organizations - Al Yasiri, Wiam Wahab Abdel-Hussein (Technium Social Sciences Journal, 2021)
This study aims to identify the effect of time management on the success of service organizations, in order to proceed with the goals that follow this study and find the relationship and influence the dimensions of each of the two variables, which is the first variable time management after the researcher chose the two methods of organization and management of goals, while the second variable was service organizations Which includes organizational performance and creative leadership, as the researcher used the descriptive approach after conducting the field study